REMOVAL OF PHOSPHORUS FROM WASTEWATER BY ADSORPTION ONTO NATURAL IRAQI MATERIALS (Journal of Engineering, 2011)
This study focused on treating wastewater to remove phosphorus by adsorption onto naturaland local materials. Burned kaolin, porcelinite, bauxite and limestone were selected to be testedas adsorption materials.The adsorption isotherms were evaluated by batch experiments, studyingthe effects of pH, temperature and initial phosphorus concentration. The results showed that at pH6, temperature 20°C and 300 mg/l initial phosphorus concentration; the sorption capacity was0.61, 9, 10 and 13 mg/g at 10 h contact time, for burned kaolin, porcelanite, limestone and bauxiterespectively. As the pH increased from 2 to 10 the removal efficiency for the materials differs inbehaviour. The removal efficiency increased from 40 to 90 % for limestone, and decreased from60 to 30 % for porcelinite. As for bauxite it increased from 60 to 90 % reaching pH 6 thendecreased to 30%. Burned kaolin showed the lowest adsorption capacities in these tests. Theadsorption isotherms showed that the Langmuir–Freundlich model significantly correlated theexperimental data for porcelinite and bauxite, whereby the Freundlich model was best forlimestone. The Freundlich and Langmuir–Freundlich models both fit for Burned kaolin. Theresults show that it is possible to adsorb phosphate from wastewater onto natural Iraqi materialand their ability could be ranged as limestone> bauxite> porcelanite> burned kaolin.